TRPV6 compound heterozygous variants result in impaired placental calcium transport and severe undermineralization and dysplasia of the fetal skeleton. Issue 9 (25th August 2018) - Burren, Christine P.; Caswell, Richard; Castle, Bruce; Welch, C. Ross; Hilliard, Tom N.; Smithson, Sarah F.; Ellard, Sian
Abstract : Transient receptor potential vanilloid 6 ( TRPV6 ) functions in tetramer form for calcium transport. Until now, TRPV6 has not been linked with skeletal development disorders. An infant with antenatal onset thoracic insufficiency required significant ventilatory support. Skeletal survey showed generalized marked undermineralization, hypoplastic fractured ribs, metaphyseal fractures, and extensive periosteal reaction along femoral, tibial, and humeral diaphyses. Parathyroid hormone (PTH) elevation (53.4–101 pmol/L) initially suggested PTH signaling disorders. Progressively, biochemical normalization with radiological mineralization suggested recovery from in utero pathophysiology. Genomic testing was undertaken and in silico protein modeling of variants. No abnormalities in antenatal CGH array or UPD14 testing. Postnatal molecular genetic analysis found no causative variants in CASR, GNA11, APS21, or a 336 gene skeletal dysplasia panel investigated by whole exome sequencing. Trio exome analysis identified compound heterozygous TRPV6 likely pathogenic variants: novel maternally inherited missense variant, c.1978G > C p.(Gly660Arg), and paternally inherited nonsense variant, c.1528C > T p.(Arg510Ter), confirming recessive inheritance. p.(Gly660Arg) generates a large side chain protruding from the C‐terminal hook into the interface with the adjacent TRPV6 subunit. In silico protein modeling suggests steric clashes between interface residues, decreased C‐terminal hook, and TRPV6 tetramer stability. The p.(Gly660Arg) variant is predicted to result in profound loss of TRPV6 activity. This first case of a novel dysplasia features severe but improving perinatal abnormalities. The TRPV6 compound heterozygous variants appear likely to interfere with fetoplacental calcium transfer crucial for in utero skeletal development. Astute clinical interpretation of evolving perinatal abnormalities remains valuable in complex calcium and bone pathophysiology and informs exome sequencing interpretation.